Expression of Tmem119/Sall1 and Ccr2/CD69 in FACS-Sorted Microglia- and Monocyte/Macrophage-Enriched Cell Populations After Intracerebral Hemorrhage - Li, Qian; Lan, Xi; Han, Xiaoning; Wang, Jian (Frontiers in Cellular Neuroscience, 2019)
Activation and polarization of microglia and macrophages are critical events in neuroinflammation and hematoma resolution after intracerebral hemorrhage (ICH). However, distinguishing microglia and monocyte-derived macrophages histologically can be difficult. Although they share most cell surface markers, evidence indicates that the gene regulation and function of these two cell types might be different. Flow cytometry is the gold standard for discriminating between the two cell populations, but it is rarely used in the ICH research field. We developed a flow cytometry protocol to identify and sort microglia and monocyte-derived macrophages from mice that have undergone well-established ICH models induced by collagenase or blood injection. In addition, we combined a recently established magnetic-activated cell separation system that allows eight tissue samples to be assessed together. This protocol can be completed within 5-8 h. Sorted cells are fully preserved and maintain expression of microglia-specific (Tmem119/Sall1) and macrophage-specific (Ccr2/CD69) markers. They retain phagocytic ability, respond to lipopolysaccharide stimulation, and engulf fluorescent latex beads. Thus, this protocol represents a very important tool for researching microglial and monocyte-derived macrophage biologic function after ICH and other brain diseases.